PENGARUH KUALITAS PRODUK DAN KEPUASAN PELANGGAN TERHADAP ELECTRONIC WORD OF MOUTH (E-WOM) PADA FASHION ONLINE SHOP JOYISM DI INSTRAGRAM - Lukluk’ Atul Bahiroh; N Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT               This study aims to determine the Effect of Product Quality and Customer Satisfaction on Electronic Word Of Mouth (E-Wom) on Joyism Fashion Online Shop in Instragram. The population in this study took from data obtained from Joyism Malang online shop customers in April-May. Sampling in this study was 92 respondents. The analytical method used is purposive sampling technique. The results in this study indicate that product quality variables have a positive and significant effect on E-WOM (Electronic Word Of Mouth). It can be seen that the calculated value is 9,791 with a significant value of 0,000. Product quality variables have a positive and significant effect on customer satisfaction that the t-count value is 2.955 with a significant value of 0,000. Customer satisfaction variables have a positive and significant effect on E-WOM (Electronic Word Of Mouth) that the t-count value is 4.211 with a significant value of 0.000. Customer satisfaction variable (Z) can mediate between product quality variables (X) against E-WOM (Y) showing the results of one-tailed probability or probability on product quality 0.00377462 <0.05.  Keyword: Product Quality, Electronic Word Of Mouth (E-WOM), Customer Satisfaction